The faces of Muslim/Christian relations: application of the Shari'ah and the rights of muslim women in Nigeria (2016)
This paper focuses on Muslim/Christian understanding of the position of the Sharī‘ah in modern Nigeria. It also examines Muslim women’s commitments to Islam and how they cope with the surroundings without submitting to a uniform, integral and singular Islamist theory on the application of Sharī‘ah. The paper makes a distinction between Fiqh and the Sharī‘ah. Furthermore, while most writings tend to view the application of the Sharī‘ah in Nigeria, whether in relations to non-Muslims or to Muslim women as being political, this paper questions this view of the application of Sharī‘ah in Nigeria and suggests that the Commonwealth of Religion and Nations political system model can help in re-directing the future relations between Muslims and Christians. These can also result in ending in ending the political pressure for Sharī‘ah courts’ convictions and other abuses of Muslim women’s rights in Nigeria and create a sustainable multicultural, religious and equitable Nigeria.